Struktur Formulaik Tayangan Sinetron Indonesia - fauzi, nanang bustanul (Studi Budaya Nusantara, 2018)
Abstract Entertainment programs on TV have become the daily consumption of entertainment community. Moreover, TV entertainment has become a new 'truth' for the life value of the viewer community. The presence of varied entertainment programs such as sitcoms, soap operas and infotainment able to get into the mindset of TV viewers. Be aware or not, variants of the entertainment program can affect the pattern of community life who consume it.Furthermore, it is believed that the variant of entertainment in a variety of television shows is not present without a specified formulaik structure. As with many aspects of life, the motion of human civilization is believed to have a skeletal structure that manifests various forms of life and life. Following the view of modern structuralism raised by the linguist from Switzerland, Ferdinand de Saussure, the existence of all that is 'ordered' and touched by the human senses is composed of two important parts of internal structure and external structure. In the language paradigm underlying Saussure's thought, language has two important parts: the Langue (inner structure) and the Parole (the outer / surface structure) that manifest the internal struture. A research on the formulary structure of the entertainment show needs to be done to find out how to structure the langue over the various pares that we enjoy as well as to see how the media contribute to the creation of such formulaik structures.